Strategi manajemen majelis ta’lim dalam mencegah eksploitasi kekerasan seksual pada anak usia dini - Armanila Armanila; Hendripal Panjaitan; Irwansyah Irwansyah; Triana Hermawati (At Turots: Jurnal Pendidikan Islam, 2022)
The ta'lim assembly is located in the Medan Labuhan sub-district. Sexual violence against early childhood in this environment is very less. Therefore, the author thinks to find out the role of the ta'lim assembly in preventing the exploitation of sexual violence in early childhood in Batang Kilat village. Child sexual abuse is a form of child abuse in which older adults or adolescents use children for sexual stimulation. The purpose of this study is to determine the role and implementation of the ta'lim assembly in preventing sexual violence in early childhood, then to find out the development of the ta'lim assembly in sexual violence in early childhood, as well as what factors cause sexual violence in early childhood. and how to prevent sexual violence against early childhood in the assembly. The research method used is a qualitative research method with a descriptive approach, with data obtained from observations, interviews and documentation. Observations and documentation were carried out to the congregation of the ta'lim assembly, while interviews were shown to local residents. The results of the study showed that there was an increase in the implementation of the ta'lim assembly activities in preventing sexual violence in children of the ta'lim assembly age. The factors that cause sexual violence in early childhood are family problems, factors from within themselves and from thsurrounding environment.